Occupational Competency Profile for Workers in Mechanical Industry Towards Sustainable Development - Affero Ismail, Affero Ismail; Arizza Zainal, Arizza Zainal; Siti Soleha Razali, Siti Soleha Razali; Norzella Bokhari, Norzella Bokhari; Reyanhealme Rohanai, Reyanhealme Rohanai (2023)
The encouragement of technology application in environmental protection is one of the major challenges faced by most industries. Human activities that harm the environment must be tackled wisely so that all efforts in maintaining a safe environment can be continued. This situation leads us to the need for preparing individuals with adequate skills and knowledge related to green skills before entering the industry. This research is conducted to identify the occupational competency profile for mechanical industry towards sustainable development. The Fuzzy Delphi Method (FDM) was utilized in this research. The FDM is a structured investigation process aimed at reaching a consensus among a group of experts on a particular topic. Five experts were involved in the first phase and eleven experts were involved in the validation process in the second phase. The lowest items score based on the expert’s consensus were rejected. Three items were rejected because of the score less than 75 per cent. The final competency profile consisting of Skill, Knowledge, and Attitude domains with 14 sub domains was constructed. The current scenario shows that people entering the industrial world lack relevant skills to work on sustainable development. These workers are classified as low-skilled workers, which means they need to be trained before entering the labor market. This study can support the development of training towards sustainability for future workers in the mechanical industry towards sustainability. Therefore, specific training related to their professional skills, especially green skills, needs to be carried out to improve their skills.